Analysis Of Legal Remedies Against Judges Decisions Regarding Evidence Owned By Good Faith Third Parties In Corruption Cases - Dewi Syahlila Arinda Putri (CV. AFDIFAL MAJU BERKAH, 2025)
The form of legal protection for third parties for evidence declared forfeited to the state is in the form of being able to submit an Objection Request to the Court that decided the corruption crime case as the main case and as a condition for third parties to obtain legal protection in the form of filing an objection request is that it must be based on good faith, namely the Third Party where the evidence is really his property that does not originate or has nothing to do with the criminal act of corruption committed by the Defendant. On the decision of the Objection Petition handed down by the Court against the Objection Petition, there is only a legal remedy of Cassation that can be filed by the Third Party as the Objection Petitioner and the Public Prosecutor as the Objection Respondent and the Cassation legal remedy can only be filed once and there is also no legal remedy of Reconsideration allowed. In the arrangement, there is no balance between the state's right to recover state financial losses that can be carried out by the Public Prosecutor and the Third Party in good faith for the return of his property, where the Public Prosecutor is provided with legal remedies in the form of being able to file a civil lawsuit through the State Attorney based on Article 32 of Law Number. 31 of 1999 concerning the Eradication of Corruption, in an effort to optimize the recovery of state financial losses. On the other hand, third parties are not provided with legal remedies if the objection filed by them on their evidence confiscated for the state in corruption crimes if the objection filed at the cassation level is rejected. The results of this study aim to provide legal protection to third parties who are in good faith over their property which is used as evidence of tipikor cases that do not belong to the defendant and are seized for the state, so that human rights in the form of property rights over third party property can be sought to be restored by being given proportional legal remedies balanced between the state through the State Attorney and third parties as citizens in a state of law.